CURRENT PROBLEMS WITH THE NOMENCLATURE OF PHYLLOSILICATES - Zvyagin B.B. (My University, 2001)
The nomenclature of phyllosilicates is discussed in relation to structural variations of layers and interlayers. Some discrepancies in the nomenclature which arose due to historical reasons and different viewpoints may be reconciled if the choice of the construction units (layers or their parts) is related to definite sets of structures for which these units are common. Features of idealized models approximating real structures should be considered for classification and derivation of nomenclature sets, whereas priority is given to structural variations before lattice and symmetry characteristics. Layer polymorphs, pseudo-polytypes, polytypes (both simple and complex), and OD structures are distinguished. Particular results obtained for micas as a model example of phyllosilicates in relation to modular structures in general are considered in an Appendix.